Analisis Pembinaan Kelompok Sadar Wisata Terhadap Kinerja Pegawai - M Inder Mawan; Jaenab Jaenab (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
The purpose of this study is to find out the description of the implementation of coaching conscious groups and their influence on employee performance. The type of research used is causal associative with quantitative methods. The population in the study tour conscious group of 200 people, and a sample of 50% of the population or 100 people with sampling techniques using simple random sampling. Data collection techniques were obtained through observation, documentation and questionnaires. To analyze the data collected, the writer uses an analysis tool consisting of: descriptive analysis, simple linear regression analysis, product moment coefficient, and hypothesis testing. Descriptive analysis results that the development of tourism awareness groups in both categories in terms of indicators of knowledge development, skills / expertise development, abilities and motivation. While the performance of employees in the high category in terms of indicators of work quality, quantity of work, effectiveness and responsibility. From the results of regression analysis and hypothesis testing that there is a significant influence of Tourism Awareness Group Development on Employee Performance. The direction of a positive relationship indicates that if the variable of guidance for the tourism awareness group is getting better the employee performance will increase